Contribution to Global Warming Potential by waste producers: Identification by reverse logistic modelling. (20th January 2019) - Šomplák, Radovan; Pavlas, Martin; Nevrlý, Vlastimír; Touš, Michal; Popela, Pavel
Abstract: An overview of relevant literature shows how supply chain and network flow models represent useful tools in the area of clean energy generation and processing related waste. This paper deals with a specific network flow problem where the mixed municipal waste as a secondary and partly renewable energy carrier is transported from waste producers (municipalities), through pre-processing facilities, to its final treatment in waste processing units and in which the optimal flow is desired. The results obtained for the minimum total costs, including treatment and transportation, correspond to production and savings of a certain amount of CO2 and other greenhouse gases which is described by Global Warming Potential (GWP). The average cost was 74 EUR/t and average GWP was 37 kg CO2eq /t. The GWP contribution varies among the waste producers as a result of treating waste in different places and various technologies. However, to identify the individual contributions, the detailed waste flow identification is required. The flow distribution is unknown due to the effect of merging and splitting waste streams in the network. For this reason, a consequent network flow problem for exact waste flows identification is proposed. The model follows the principle ideas of multi-commodity network flow modelling and it reveals the variability of cost and GWP contribution for all producers in the investigated area. The proposed method has been tested through a case study considering treatment of mixed municipal waste. The results obtained by the original implementation in GAMS are presented and discussed in detail. The GWP contribution varied between −173 and 880 kg CO2eq /t and significant waste producers were identified in the network regarding GWP. The results are important for setting the target for emission reduction in individual regions and for particular producers. The principle can be applied in general to any commodity and network flow problem. Highlights: Emission, processing and cost analysis in a feasibility study for waste treatment. Branching network structure lead to the loss of information in producer waste flow. A new computational approach extends a basic flow and capacity allocation problem. Waste flows are identified to evaluate GWP contribution of the particular producer.